Program Pendampingan Pendidikan Akhlak dan Kesadaran Hukum bagi Warga Pondok Boro Semarang - Nuridin Nuridin; Ira Alia Maerani; Ferry Firmawan (Jurnal Pengabdian KOLABORATIF, 2024)
Semarang is the capital of Central Java which continues to improve and improve. So the existence of residents living in bedang-bedang around Kanjengan is of concern to the Semarang City Government to be placed in relatively adequate locations. They were then moved to an area known as Pondok Boro. This location is in Trimulyo Village, Genuk, Semarang. This community service is part of the da'wah to develop science and knowledge, as well as in the context of implementing the tri dharma of higher education. The method of implementing community service is through mentoring, lectures, and training which is based on the idea of the need for moral education and legal awareness for Pondok Boro residents. Training and education process on morals and morals so that it is hoped that a society that is full of Pancasila values will grow. Values of belief in one almighty god, just and civilized humanity, values of indonesian unity, democracy led by wisdom in deliberation and/representation, and prioritizing social justice for all Indonesian people. The enthusiasm of the residents was quite good with their active participation in the training session marked by the questions asked. The activity was also continued by the Lazis Sultan Agung Volunteer Team by involving students as volunteers and teaching staff at the Al-Qur'an Reading Park at the Pondok Boro location as an integration program.